COMPREHENSIVE MIDWIFERY CARE FOR MRS. M AT TRI HASANAH INDEPENDENT MIDWIFERY PRACTICE, SUBULUSSALAM CITY IN 2026 - Rosaiba Rambe; Rahayu Ningsih; Ricca Nophia Amra; Ratnawati Bancin; Fitriani Bancin, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Maternal and neonatal mortality rates remain critical indicators of healthcare quality, posing a significant challenge in Subulussalam City, where 18 maternal and 25 neonatal deaths were recorded in 2023. As a preventive measure, comprehensive midwifery care (Continuum of Care) is essential to systematically detect risks and minimize complications from pregnancy through family planning. This descriptive case study aimed to provide continuous, high-quality midwifery care using Varney's management method and SOAP documentation for Mrs. M (28 years old, G2P1A0) at PMB Tri Hasanah, Subulussalam City, from March to July 2026. Primary data were gathered through continuous interviews, physical examinations, and clinical observations. The results showed that third-trimester pregnancy progressed normally with appropriate management of physiological discomforts. Delivery was spontaneous and smooth, resulting in a healthy male infant weighing 3,800 grams and an intact maternal perineum with no lacerations. The postpartum period, neonatal care, and family planning services, which resulted in selecting a breastfeeding-safe contraceptive method, were successfully completed without pathological complications. In conclusion, the application of comprehensive midwifery care is proven effective in ensuring maternal and newborn safety, preventing fatal complications such as postpartum hemorrhage, and boosting family planning engagement.